Influence Analysis the Technology Acceptance Model Approach on User Satisfaction and Repurchase on the KAI Access Application Using the SEM Method - Kartika, Nuarita Tri; Waluyo, Minto (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
The KAI Access application is a transportation service application from PT Kereta Api Indonesia. From a survey conducted by researchers, there is application dissatisfaction by users. This study aims to determine the effect of five TAM variables on user satisfaction and repurchase. In accordance with the research objectives, several TAM variables will be used, namely actual use, perceived ease of use, perceived usefulness, perceived risk, and perceived trust. It will also be known the effect of TAM variables on application user satisfaction, and repurchase of train tickets by application. After analyzing with SEM coherently, the results show that the actual use variable has a C.R. value of 6.095, has a positive and significant value on application user satisfaction. With a C.R. value of 7.668, the perceived usefulness variable has a significant positive value on application user satisfaction. With a C.R. value of 6.763, the perceived risk variable has a significant positive value on application user satisfaction. The perceived trust variable in the application has a C.R. value of 6.094 and has a significant positive value on application user satisfaction. With a C.R. value of 7.434, the application user satisfaction variable has a positive and significant value on the repurchase of train tickets through the application.